Investigating Students’ Perception of Effective EFL Teachers’ Teaching: A Survey Study at One of the State Junior High Schools in Indonesia - Wahyudi, Dedy; Losari, Novika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The study aims at investigating students’ perception of effective EFL teachers’ teaching at one of the State Junior High Schools in Indonesia. The sample in the study was 132 students from 5 classes of State Junior High Schools 40 Pekanbaru. It was selected by using simple random sampling technique. This study employed a survey research design in terms of descriptive quantitative approach. The result in the study showed that students’ perception of effective EFL teachers’ teaching were very positive for each indicator namely delivery, fairness, knowledge and credibility, and organization and preparation. It revealed that the perception of effective EFL teachers’ teaching showed highest percentage of the statement of strongly agree such as effective teachers are friendly in rapport category, effective teachers give clear explanations in delivery category, effective teachers treat all students fairly in fairness category, effective teachers have a good knowledge of vocabulary in knowledge and credibility category, and effective teachers make their own supplemental material in organization and preparation category. It can be concluded that the students’ perception of effective EFL teachers’ teaching should be well identified by English teachers for the remarkable progress of teaching English in the classroom. Key words: Students’ Perception, Effective Teaching, EFL Teachers